Ductal Carcinoma In Situ Simultaneously Involving the Breast and Epithelial Inclusions in an Ipsilateral Axillary Lymph Node. (September 2018) - Commander, Leah A.; Ollila, David W.; O'Connor, Siobhan M.; Hertel, Johann D.; Calhoun, Benjamin C.
Benign cystic epithelial inclusions with squamous, glandular, or Müllerian phenotypes are known to occur in the axillary lymph nodes of patients with benign and malignant breast disease. Careful evaluation of hematoxylin and eosin–stained slides and correlation with the histologic findings in the ipsilateral breast are paramount in evaluation of suspected benign inclusions. In this case of ductal carcinoma in situ (DCIS) of the breast in a 73-year-old woman, DCIS also involved epithelial inclusions in an ipsilateral axillary lymph node. The recognition of these benign epithelial elements, and awareness that they can be involved by DCIS, is crucial to avoid the overdiagnosis of metastatic carcinoma.